Towards Canine Rabies Elimination in KwaZulu–Natal, South Africa: Assessment of Health Economic Data. Issue 4 (21st November 2014) - Shwiff, S. A.; Hatch, B.; Anderson, A.; Nel, L. H.; Leroux, K.; Stewart, D.; de Scally, M.; Govender, P.; Rupprecht, C. E.
Summary: Rabies remains a significant problem throughout much of the developing world. An estimated 69 000 people die annually from exposure to rabies. Most of these deaths are the result of being bitten by a rabid dog. Mass vaccination campaigns targeting dogs have been implemented around the world in an attempt to control or eliminate canine rabies. We analysed the vaccination and cost data for a campaign in the KwaZulu–Natal province of South Africa; we found that the cost per dog vaccinated to be 6.61 for mass campaigns and 5.41 for local campaigns. We also estimated the cost of human post‐exposure prophylaxis (PEP). The cost of PEP is approximately 64.50 on average per patient, and 333 on average for the 9% of patients who receive RIG. We also found that the districts that vaccinated the most dogs per capita experienced the highest rates of human treatment and thus had the highest PEP costs.